Antibiotic-induced Disruption of Intestinal Microbiota Contributes to Failure of Vertical Sleeve Gastrectomy. Issue 6 (June 2019) - Jahansouz, Cyrus; Staley, Christopher; Kizy, Scott; Xu, Hongliang; Hertzel, Ann V.; Coryell, Jessi; Singroy, Stephanie; Hamilton, Matthew; DuRand, Meri; Bernlohr, David A.; Sadowsky, Michael J.; Khoruts, Alexander; et al.
Abstract : Objective: The aim of this study was to test whether the perioperative composition of intestinal microbiota can contribute to variable outcomes following vertical sleeve gastrectomy (VSG). Summary of Background Data: Although bariatric surgery is the most effective treatment for obesity, metabolic outcomes are variable. Methods: Diet-induced obese mice were randomized to VSG or sham surgery, with or without exposure to antibiotics that selectively suppress mainly gram-positive (fidaxomicin, streptomycin) or gram-negative (ceftriaxone) bacteria on postoperative days (POD) 1-4. Fecal microbiota was characterized before surgery and on POD 7 and 28. Mice were metabolically characterized on POD 30-32 and euthanized on POD 35. Results: VSG resulted in weight loss and shifts in the intestinal microbiota composition relative to sham-operated mice. Antibiotic exposure resulted in sustained reductions in alpha (within-sample) diversity of microbiota and shifts in its composition. All antibiotic treatments proved to be detrimental to metabolic VSG outcomes, regardless of antimicrobial specificity of antibiotics. These effects involved functionally distinct pathways. Specifically, fidaxomicin and streptomycin markedly altered hepatic bile acid signaling and lipid metabolism, while ceftriaxone resulted in greater reduction of key antimicrobial peptides. However, VSG mice exposed to antibiotics, regardless of their specificity, had significantly increased subcutaneous adiposity and impaired glucose homeostasis without changes in food intake relative to control VSG mice. Conclusion: Dysbiosis induced by brief perioperative antibiotic exposure attenuates weight loss and metabolic improvement following VSG. Potential mechanisms include disruption of bile acid homeostasis and reduction in the production of gut antimicrobial peptides. Results of this study implicate the intestinal microbiota as an important contributor to metabolic homeostasis and a potentially modifiable target influencing clinical outcomes following VSG. Abstract : Supplemental Digital Content is available in the text